Analysis and forecasting of self-similar financial time series - Moklyachuk, M.; Zrazhevsky, A. (Інститут математики НАН України, 2006)
Time series of prices of MSFT ticker are considered. Results on selfsimilarity
of this time series are presented. A method of prediction from FARIMA model for long-range dependent time series is described. This method is used for prediction of MSFT time series of prices that exhibits
long-range dependence with the Hurst parameter close to 1.